Good University Governance and Its Role in Reaching Quality Education SDGs - Amir Firmansyah; Zul Karnen; Suparji Suparji; Aris Machmud (Contrarius Indonesia, 2026)
This study examines the increasing demands of globalization by asserting that higher education institutions must develop governance systems that operate effectively and ensure accountability. It argues that the implementation of Good University Governance functions as a strategic instrument to reinforce transparency, accountability, and participatory management within higher education institutions. The study investigates whether such implementation can significantly enhance educational quality in accordance with sustainable development objectives. Employing a normative legal research method, this research applies statutory, conceptual, and comparative approaches, including a comparison with governance practices in Malaysia and Singapore. The findings demonstrate that first, the implementation of Good University Governance substantially improves the quality of university governance by promoting institutional transparency, accountability, and responsiveness to societal needs. Second, higher education institutions encounter persistent challenges in implementing Good University Governance, particularly in relation to inadequate infrastructure, limited human resource capacity, regulatory inconsistency, and weak monitoring and transparency mechanisms. Third, the study formulates legal strategies that prioritize regulatory strengthening, effective supervision, protection of stakeholder rights, and the integration of technology to establish adaptive, transparent, and accountable governance systems that support the realization of quality education within the framework of sustainable development.